How a holobiome perspective could promote intensification, biosecurity and eco-efficiency in the shrimp aquaculture industry - Gutiérrez-Pérez, Eric D.; Vázquez-Juárez, Ricardo; Magallón-Barajas, Francisco J.; Martínez-Mercado, Miguel Á.; Escobar-Zepeda, Alejandra; Magallón-Servín, Paola (Frontiers in Marine Science, 2022)
The aquaculture industry faces many challenges regarding the intensification of shrimp rearing systems. One of these challenges is the release of excessive amounts of nitrogen and phosphorus into coastal areas, causing disruption in nutrient cycling and microbial equilibrium, which are important for coastal productivity. Biosecurity within the shrimp rearing systems can also be compromised by disruption to the nutrient fluxes, and as consequence the microbiome of the system. In certain conditions, these changes could lead to the blooming of potentially pathogenic bacteria. These changes in the external microbiome of the system and the constant fluctuations of nutrients can affect the intestinal microbiome of shrimp, which is involved in the growth and development of the host, affecting nutrient absorption, regulating metabolic processes, synthesising vitamins, modulating the immune response and preventing growth of pathogenic bacteria. It has been suggested that specific changes in the intestinal microbiome of Litopenaeus vannamei may be an avenue through which to overcome some of the problems that this industry faces, in terms of health, growth and waste. Recent research, however, has focussed mainly on changes in the intestinal microbiome. Researchers have overlooked the relevance of other aspects of the system, such as the microbiome from the benthic biofilms; zooplankton, plankton and bacterioplankton; and other sources of microorganisms that can directly affect the microbial status of the intestinal and epiphytic communities, especially in rearing systems that are based on intensification and microbial maturation processes, such as a biofloc system. It is therefore necessary to place holobiome studies into context, including the ‘holobiome of the aquaculture system’ (microbiomes that make up the culture system and their interactions) and not only the intestinal microbiome. Thus, we describe factors that affect the shrimp microbiome, the methodology of study, from sampling to bioinformatic workflows, and introduce the concept of the ‘holobiome of the aquaculture system’ and how this enables us to promote the intensification, biosafety and eco-efficiency of shrimp farming. The holobiome perspective implies a greater investment of resources and time for research, but it will accelerate the development of technology that will benefit the development and sustainability of the aquaculture industry.